Contracting with Gharar (Uncertainty) in forward contract: What does Islam says? - Nadhirah, Nordin; Normadiah, Daud; Sumayyah, Abdul Aziz (Canadian Center of Science and Education, 2014)
The forward contract is one of derivative instruments. The value of this contract is derived from the values of underlying assets such as commodities, equities, and currencies. Muslim scholars differ on the permissibility of forward contracts. Among the key issues raised in the forward contract is the issue of gharar. In general, gharar means an excessive uncertainty and risk. However, not all contracts containing the element of gharar void the contract. This article attempts to formulate a parameter for gharar that voids the contract based on the opinions of classical and current scholars. It also analyses the elements of gharar that exist in forward contracts of crude palm oil in Malaysia. This study uses a thematic analysis approach to explain the data collected through secondary sources and interviews with few individuals involved in this industry. Based on the analysis of forward contracts on the parameter of gharar, the finding of this research indicates that the issue of gharar exists in forward contracts does not void the contracts.